Підвищення завадостійкості демодулятора у системах коміркового зв’язку - Максимів, Іван Петрович (Національний університет "Львівська політехніка", 2013)
Дисертаційну роботу присвячено збільшенню місткості існуючих систем зв’язку шляхом зменшення порогу завадостійкості детектора приймача зі збереженням динамічних властивостей пристрою. У дисертаційній роботі проведено теоретичне дослідження оригінального модифікованого фазового детектора у режимі з використанням складних фазомодульованих сигналів, характерних для сучасних систем коміркового зв’язку. Отримано аналітичні вирази для лінійної моделі модифікованого детектора які свідчать про можливість зменшення сигналу розузгодження без зміни швидкості передавання. Реалізовано імітаційну модель модифікованого детектора за допомогою програмних засобів Matlab та перевірено її адекватність. Вперше отримано залежності BER від SNR для сучасних систем зв’язку з використанням модифікованого детектора. Надано рекомендації щодо значень параметрів фільтрів, які використовуються у приймачі. Це надало можливість при проектуванні таких систем розраховувати на впевнену роботу за умови високого рівня завад або на більшу кількість одночасно присутніх абонентів. Отримання результатів моделювання, які показали можливість значного підвищення місткості систем коміркового зв’язку на 20-35%. Диссертационная работа посвящена увеличению емкости существующих систем связи путем уменьшения порога помехоустойчивости детектора приемника с сохранением динамических свойств устройства. В диссертационной работе проведено теоретическое исследование оригинального модифицированного фазового детектора в режиме с использованием сложных сигналов с фазовой модуляцией, характерных для современных систем сотовой связи. Получены аналитические выражения для линейной модели модифицированного детектора свидетельствующие о возможности уменьшения сигнала рассогласования без изменения скорости передачи. Реализовано имитационную модель модифицированного детектора с помощью программных средств Matlab и проверено её адекватность. Впервые получены зависимости BER от SNR для современных систем связи с использованием модифицированного детектора. Даны рекомендации относительно значений параметров фильтров, используемых в приемнике. Это позволило при проектировании таких систем рассчитывать на уверенную работу при высоком уровне помех или на большее количество одновременно присутствующих абонентов. Получение результатов моделирования, которые показали возможность повышения емкости систем сотовой связи на 20-35%. The dissertation is dedicated to increasing the capacity of existing communication systems by reducing the threshold noise immunity of the receiver's detector preserving the dynamic properties of the device. In work carried out theoretical study of the original modified phase detector in modes with using complex phase shifted signals which take a place in modern cellular communication systems. The analytical expressions for the linear model of modified detector showed the possibility of reducing the signal error ratio without changing transmission speed rate. Using these mathematical models the simulation model of modified detector was implemented. The model was implemented using Matlab software. The adequacy of received imitational model was tested by plotting a diagram of depending of frequency distortion permissible values to SNR and by plotting a diagram of depending BER to SNR values, which correspond to existing values shown in modern literature. The adequate imitational models of CDMA cellular channel and TETRA radio channel were created and the noise immunity of OQPSK and 8PSK signals was investigated. During this work, it was determined the relationship between BER and SNR for classical phase detector and detector, modified by the system of narrowband proportional-integrated filters (PIF). The results of simulation of modified synchronous phase detector showed the possibility of an increase of noise immunity of receiving signals with phase shift keying and the ability of the modified detector to detect OQPSK and 8PSK signals even when signal strength is less than the capacity of obstacles. The detection quality of modified detector is higher than in classical detector. Modified phase detector has better noise immunity and in theory can improve existing wireless communications networks. First obtained the BER to SNR ratio for current communication systems using the modified detector. Received diagrams confirm the efficiency of modified detector. The recommendations on the parameters of filters used in the receiver were provided. This enabled during the design of such systems to rely on solid performance at high noise level or a greater number of users simultaneously present. Getting the simulation results, which showed a significant opportunity to increase the capacity of cellular communication systems by 20-35%.
Повышение помехоустойчивости демодулятора в системах сотовой связи
Increasing noise immunity of demodulator in cellular communication systems
Keywords: завадостійкість; місткість системи зв’язку; відношення сигнал-шум; демодулятор; OQPSK; 8PSK; помехоустойчивость; емкость системы связи; отношение сигнал-шум; демодулятор; noise immunity; communication systems capacity; BER; SNR; demodulator